(untitled) (Journal of Applied Learning and Teaching, 2022)
This review paper summarises direct experience with and studies of low-fee private (LFP) schools in sub-Saharan Africa (SSA). Parental fee payments mean a direct contractual link between family and school that is not present at government schools: it means that teachers must show up and teach most of the time, and look after the children in their charge for the duration of the school day. This schooling phenomenon has its roots in the 1990s, but despite being directly accountable, low-free private schools have not proven a solution to the challenge of low educational quality in SSA school systems. In this paper, I will describe the development of this shadow system, the scientific studies on the pros and cons of these schools as well as discuss the reasons why even the most structured LFP schools have not lived up to their supposed promise.